A new strategy of transforming an ACQ compound into an AIE theranostic system for bacterial imaging and photodynamic antibacterial therapy. Issue 4 (25th March 2023) - Xu, Lijing; Zhai, Jiadai; Han, Xue; Shang, Wenxue; Chen, Mengna; Xu, Yanling; Cui, Xinyi; Zu, Guohao; Sang, Feng; Zhang, Bin
Abstract: An organic chemical with fluorescence quenching properties [aggregation‐caused quenching (ACQ)] may often be transformed by adding functional groups that cause aggregation‐induced emission (AIE) to its molecular scaffold. Such structural change techniques, however, sometimes require challenging chemical reactions. SF136 is a type of chalcone, and it is an typical ACQ organic compound. In this study, cationic surfactants like hexadecyltrimethylammonium bromide (CTAB) and polyethyleneimine (PEI) were used to convert the ACQ compound SF136 into an AIE compound without adding any AIE structure units. In comparison to SF136, the SF136‐CTAB NPS system not only demonstrated improved bacterial fluorescence imaging capabilities, but also increased photodynamic antibacterial activity, which is connected to its improved targeting and reactive oxygen species (ROS) production abilities. It is a promising theranostic substance against bacteria owing to these enhanced qualities. Other ACQ fluorescent compounds may also benefit from using this approach, broadening the scope of their potential applications. Abstract : The SF136 can be adapted by CTAB to a diagnostic system with dual functions of bacterial fluorescence imaging and antimicrobial activity.